Understanding criminal decision-making: links between honesty-humility, perceived risk and negative affect - Chatzimike Levidi, Myrto Dafni (Psychology, crime & law, 2024)
The integrative model of criminal choice proposes that cognitive and/or affective appraisals partially mediate the personality-crime relationship. The current study tests the integrated model of criminal choice across three different levels of subjective apprehension risk. Participants made hypothetical criminal choices in response to three vignette scenarios presenting criminal opportunities varying in the implied risk of apprehension. Consistent with the integrated model of criminal choice, when risk of apprehension was not manipulated, cognitive and affective appraisals (perceived risk and negative affect) partially mediated the relationship between personality (honesty-humility) and criminal choice. Higher levels of honesty-humility predicted increased perceived risk and negative affect, which in turn predicted decreased intentions to offend. When risk of apprehension was experimentally increased, personality did not affect either variable. As predicted, in both baseline and increased levels of risk of apprehension, higher levels of honesty-humility, perceived risk, and negative affect were found to significantly predict lower intentions to offend. Additionally, decreased perceived risk predicted reduced negative affect. These findings suggest that the mediating relationship between personality and crime may be dependent on the level of subjective risk of apprehension. Future studies may investigate whether different levels of situational risk moderate the relationship between personality and cognitive/affective appraisals.